Optimalisasi Pembinaan Narapidana Anak: Analisis Hambatan dan Strategi di Lembaga Pembinaan Khusus Anak - Permatasari, Berliana Dian; Nadiroh, Nadiroh; Kardiman, Yuyus (Journal of Moral and Civic Education, 2025)
This article examines the application of the character values ​​of independence and discipline to child rehabilitation in Special Child Development Institutions (LPKA) in Indonesia. Using a systematic literature review (SLR) approach, this study analyzes relevant data to assess the effectiveness of existing programs, which encompass personal, intellectual, skills, physical, and spiritual development, in accordance with national regulations. Although these programs contribute positively to character development, their implementation faces significant challenges, primarily due to limited funding, inadequate facilities, and a lack of qualified human resources. These obstacles directly impact the primary objective of LPKA to prepare children for successful reintegration with a strong sense of independence and community discipline. To address these challenges, this study recommends implementing a collaborative model with the Ministry of Education, modeled after Malaysia, to address human resource limitations. A major limitation of this study is its reliance on secondary data through the SLR method, which does not incorporate empirical evidence from field observations. Therefore, future research should incorporate primary data to provide a more comprehensive understanding of this topic.